Spying on the South [compact disc, unabridged] : an odyssey across the American divide - Horwitz, Tony, 1958-2019- (Penguin Audio, 2019)
Tony Horwitz retraces Frederick Law Olmsted's epic journey across the American South in the 1850s, as he too searches for common ground in a dangerously riven nation.